ANALISIS PENGELOLAAN SAHAM SYARIAH HIGH DIVIDEND SEBAGAI PORTOFOLIO WAKAF SAHAM - Deryandri; Indra Indra (Tazkia Islamic Finance and Business Review, 2025)
Indonesia with a Muslim majority inherently provides potential for the development and utilization of productive waqf as a financial instrument for social welfare and economic growth. Stock waqf is one of the productive waqf that is quite potential to be developed because it provides the potential for quite large profit sharing with minimal risk if placed in stocks that are fundamentally strong and liquid to maintain the sustainability of waqf assets in the long term. This study aims to analyze the returns and risks of sharia stock portfolios on IDX High Dividend 20 stocks and including LQ45 stocks if placed as waqf objects. In addition, it also analyzes the strategy for implementing stock waqf portfolios for wakif, nazhir and regulators. This study uses two methods to answer the problem formulation, namely Return Portfolio and Risk Portfolio. Furthermore, for the second research question, in-depth interviews and literature studies are used. The results of the study prove that the strategy of forming a portfolio based on dividend yield on stocks that fall into the criteria of IDX High Dividend 20, LQ45 and JII has been proven to consistently increase returns (yield) and total returns with increasing dividend yield. Portfolio 4 which focuses on stocks with dividend yield ≥ 5% provides the highest return (yield) of 17.06% per year, this is also a picture of the yield if applied as a stock waqf portfolio and the total return is also the highest at 18.20% per year, this is also a picture of the yield if applied as a cash waqf investment portfolio or stock futures waqf. In addition, this study emphasizes the importance of education and increasing the competence of nazir in sharia financial literacy and stock waqf management. Collaboration between stakeholders, including nazir, financial institutions, and regulators, is needed to maximize the potential of stock waqf. Effective risk management and transparency in reporting are also key elements to maintain investment stability and increase public trust.